Augmented Reality Application for Optical Character Recognition - Nandan, Kumar N; Wan Nor Al-Ashekin, Wan Husin (INTI International University, 2024)
Augmented Reality (AR) technology has become popular for improving user experiences by superimposing virtual features on the real world. OCR is another recent method for extracting text from photos or real-world items. AR and OCR are combined in a new software that provides an immersive and engaging experience. The proposed AR-based OCR system uses Firebase as a backend. Users can point their smartphones at papers, signs, or other textual material to use AR, which will automatically recognizeand extract the content. This extracted content can be translated, converted to text-to-speech, or shared on social media. Storage and management of recognizedtext data is reliable and scalable with the Firebase database connector. The Firebase Realtime Database can immediately sync extracted text across several devices for user collaboration and sharing. Firebase Authentication can authenticate and authorizeusers for safe OCR access. The programuses image processing for text extraction, OCR models for accurate recognition, and AR frameworks like ARCore (Android) and ARKit (iOS). The application will be linked to the Firebase backend using SDKs and APIs for real-time data synchronizationand safe data storage. The AR-based OCR application has great promise in education, logistics, retail, and other industries. It can extract text from physical documents, increase accessibility for visually challenged people, and translate foreign languagetext in real time. Firebase's backend database solution meets the application's needs for scalability, dependability, and data security.